(untitled) (Journal of Sciences & Technology, 2016)
These The take into account of the three-body monopole effects can solve the spectroscopic problems involved in certain nuclear properties, for which the two body realistic interactions failed. In order to study and to understand the role of these effects, calculations in the shell model of nuclear structure were carried out to develop the two body matrix elements of N-N interaction. Their application on 136Sb nucleus with four valence particles in addition to the inert core 132Sn has a great importance. This nucleus with N 82 is currently the most experimentally studied in this mass region. The first excited state, dominated by p(1g7/2)1n(2f7/2)3 configuration, obtained in this work reproduces the experimental one.